25 EVALUATION OF PATIENTS PRESENTING WITH TIA IN THE AMAU AND TIA FAST ASSESSMENT CLINICS - ARE WE MEETING ESO GUIDELINES?. (25th October 2022) - Hearne, S; Costelloe, R; Murphy, S; Kelly, P; McGorrian, C; Marnane, M
Abstract: Background: The European Stroke Organisation published guidelines on the management of Transient Ischaemic Attack (TIA) in 2021. Specialist review of suspected TIA is recommended within 24-hours of symptom onset in a TIA clinic. They suggest using CT or MR angiogram for additional confirmation of large artery stenosis of >50%. They advise against the use of prediction tools alone e.g. ABCD2 score when identifying high-risk patients. Dual antiplatelet therapy is recommended short-term in high risk, non cardio-embolic TIA patients. This audit evaluates if these guidelines are being followed in our institution. Methods: We evaluated all patients attending the TIA clinic and the Acute Medical Assessment Unit (AMAU) with suspected TIA over a three-week period in 2021 in a single tertiary referral centre. Retrospective data was collected based on chart review. Results: Twenty patients underwent review in the TIA clinic and eight in the AMAU with suspected TIA in the chosen time period. One patient (3.5%) was seen within 24 hours from symptom onset, 2 were seen within 24-36 hours (7.1%), 4 patients (14.2%) were seen within 36-72 hours, 21 patients (75%) were seen >72 hours after symptom onset. In all patients who had a doppler US showing >50% carotid stenosis, a CT angiogram was performed. ABCD2 scores were recorded but used in combination with clinical judgment. All patients with high-risk, non-cardioembolic TIA received early, short-term dual antiplatelet therapy. Conclusion: The diagnostic methods and treatment strategies in place for patients attending the TIA clinic or AMAU with TIA were in keeping with the recently published ESO guidelines. However, there was a time delay from symptom onset to time of review in many patients. Further studies are indicated to identify the potential mechanisms behind these delays. Interventions to ensure that we are meeting this 'time-to-review' target in patients could be implemented, ensuring high quality, evidence-based care.